(3cJGH aj GdLZQGajGs
(3ChdgG (B:s
(3NjQ eG GSJaJM Hg GdcdGe MeO GdhGMO GdYdGe aEfi fSNJ gPg GdLZQGajI ef fSNI fSNJ ef LZQGajI GdZRGQi s
(3BNQgG (B:s
(3hef eHYK GdfHi Udi Gddg Ydjg hSde Zdi Mjf JeGe gPG GdcJGH GdeSei HGdLZQGajI s
(3GYJeO Ydi LZQGajI GdaRGQi hCdag SfI (B692s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
Keywords: (3GdLZQGajG h GdHdOGfs